Comparison between critical velocity and anaerobic threshold in deep water running - Fernando de Oliveira; Adriano Lima-Silva; Fábio Nakamura; Leandro Albuquerque da Silva (Universidade Federal de Santa Catarina, 2006)
The comparison between critical velocity and anaerobic threshold has not been investigated in deep water running. Therefore, the aim of this study was to compare these two variables in this activity. Ten subjects of both sexes (23.1 ± 2.2 years, 174.0 ± 10.0 cm, 66.5 ± 18.7 kg) and without previous practice in the activity weresubmitted to: 1) two to four familiarization sessions; 2) a progressive test, starting with velocity of 0.15 m.s-1 and increments of 0,05 m.s-1 every three minutes; 3) three tests of constant velocities in different days, with velocities ranging from 0.25 to 0.40 m.s-1. The comparison between anaerobic threshold (velocity at 3.5 mM) and critical velocity (identified by three different equations) was performed by analysis of variance and the Bland-Altman method. No significant differences were identified among the variables (p = 0.28), however, the limits of agreement provided by the Bland-Altman plots were very large (between -0.054 e +0.080 m.s-1). These results suggest caution when using the critical velocity to estimate the anaerobic threshold. RESUMO A comparação entre velocidade crítica e limiar anaeróbio não tem sido realizada em atividades como corrida aquática. Assim, o objetivo desse estudo foi comparar essas duas variáveis, ambas identificadas nesse tipo de exercício. Dez sujeitos de ambos os sexos (23,1 ± 2,2 anos, 174,0 ± 10,0 cm, 66,5 ± 18,7 kg), sem experiência prévia na modalidade, foram submetidos a: 1) de duas a quatro sessões de familiarização; 2) um teste de intensidade progressiva, com velocidade inicial de 0,15 m.s-1 e incrementos de 0,05 m.s-1 a cada três minutos; 3) três testes de velocidade constante, realizados em dias diferentes, com velocidades entre 0,25 a 0,40m.s-1. A comparação entre o limiar anaeróbio (velocidade referente a 3,5mM) e a velocidade crítica (obtida por três equações diferentes) foi feita pela análise de variância (ANOVA) e técnica de Bland-Altman. Não foram encontradas diferenças significantes entre as variáveis estudadas (p = 0,28), mas a faixa de erro dos limites de concordância estabelecidos pela plotagem de Bland-Altman foi demasiadamente alta (entre -0,054 e +0,080 m.s-1). Esses resultados sugerem cautela na utilização da velocidade crítica como indicador do limiar anaeróbio.